Pengaruh Media Teknologi Informasi Komputer Dan Kemampuan Pedagogik Terhadap Hasil Belajar Ipa Pada Siswa Kelas X Sman I Tanjung Bumi Bangkalan - Kuswanto, Gerry; Wahyuningtyas, Sri; Sunardjo, Sunardjo (Penerbit STKIP PGRI Bangkalan, 2024)
The aim is to test, prove and describe whether or not there is an influence of ICT-based learning media and teacher pedagogical competence on the learning outcomes of class X science subject matter at SMAN 1 Tanjung Bumi. This research uses a quantitative type of research. Quantitative research is research in the form of numbers with statistical analysis. The design of this research is ex post facto, that is, data is collected after all the events in question have taken place without any treatment. Based on Table 4.5. It can be read that the Fcount value = 4,843 with a significance (Sig.) of 0.032. Meanwhile, to test the proposed hypothesis, it is accepted or rejected by looking at the F value and significance (Sig.). the conditions for acceptance or rejection occur if the value of Fcount > Ftable and Significance (Sig.) < 0.05 (Alpha) then H0 is rejected and Ha is accepted. At a significance level of 5% and df 2, F table = 3.22. From the output it can be seen that the significance value (asymp sig.) is 0.032. Because the significance value is <0.05, Ho is rejected. So it can be interpreted that there is an interactive influence between the use of ICT-based learning media and pedagogical abilities on science learning outcomes.